Performance Optimization of Biomass Fly Ash as a Partial Cement Replacement in Concrete Based on Compressive Strength, Sorptivity, and Half-Cell Potential - Nur Okviyani; Yusman Yusman; Irma Ridhayani; Muhammad Isra; Akbar Indrawan Saudi; Ainun Jariah Hilal Anshary; Amalia Nurdin (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2026)
The use of biomass fly ash (BFA) as a supplementary cementitious material offers a practical approach to reducing cement consumption while enhancing concrete durability. This study evaluates the effect of BFA as a partial cement replacement on the mechanical and durability performance of concrete produced with river sand and freshwater. BFA was incorporated at replacement levels of 0%, 5%, 15%, and 25% by cement mass, with a constant water-to-binder ratio of 0.40. Compressive strength was tested at 7, 28, and 91 days, sorptivity was measured at 28 and 91 days, and the corrosion probability of embedded reinforcing steel was assessed using the Half-Cell Potential method from 7 to 91 days. The results show that BFA reduced early-age strength, especially at 15% and 25% replacement, due to the slower development of pozzolanic reactions. However, the later-age performance improved markedly. At 91 days, the mixture containing 25% BFA achieved the highest compressive strength of 36.46 MPa, representing a 27.48% increase over the control mixture. This mixture also produced the lowest sorptivity value of 0.91 mm, indicating reduced capillary water absorption. Half-Cell Potential results showed that all mixtures reached the low corrosion probability range at 91 days, with the 25% BFA mixture recording -59.13 mV. Overall, 25% BFA provided the best balance between compressive strength, water absorption resistance, and corrosion-related durability. Keywords: biomass fly ash; compressive strength; concrete durability; half-cell potential; sorptivity